Fake alpha - Marcel Müller; Tobias Rosenberger; Marliese Uhrig-Homburg (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2017)
Why do investors entrust active mutual fund managers with large sums of money while receiving negative excess returns on average? Our explanation is that investors have a coarser information set than fund managers which leads them to systematically misinterpret managers' skill. When investors are unable to correctly quantify risk because they have no knowledge of factor investing on beyond-market-risk factors, Fake Alpha strategies based on factor investing look like skill from the investors' perspective. As running such strategies is relatively cheap for the managers, the investors' coarser information set misleads them to invest beyond the point of zero excess returns in equilibrium. We confirm our theory by analyzing the sample of US equity active managed mutual funds and find significant evidence of decreasing returns to scale at the fund level as well as negative excess returns to investors in equilibrium states.
Keywords: G23; G11; G20; 330; mutual funds; active management; managerial skill; alpha